Evaluating Clinical Staff Perceptions of EHR Usability, Satisfaction, and Adaptation to a New EHR: A Multisite, Pre–Post Implementation Study - Diamond, Courtney J.; Elias, Jonathan E.; Lee, Rachel Y.; Jia, Haomiao; Abramson, Erika L.; Ancker, Jessica S.; Bostwick, Susan; Cato, Kenrick D.; Trepp, Richard; Lewis, Rachel A.; Crimmins, Timothy J.; Rossetti, Sarah C. (Applied Clinical Informatics, 2025)
The adoption of electronic health records (EHRs) into clinical practice has changed clinical workflows and, in some cases, increased documentation burden and clinician burnout. Identifying factors associated with perceived EHR usability after the implementation of a new EHR may guide efforts to reduce burden and burnout.This study measured: (1) group-level perceptions of EHR usability pre- and postimplementation of a new EHR; (2) adaptation to the new EHR; and (3) the effects of clinical role, setting, and specialty on these measures.Pre- and postimplementation surveys were sent to clinical staff at two academic medical centers (AMC A and AMC B), each part of the same Northeast health system where one instance of a new EHR was implemented starting in 2020. The surveys measured constructs from the Health Information Technology Usability Evaluation Scale (Health-ITUES) and Health Information Technology Adaptation survey. Unpaired t-tests assessed changes in group-level scores from pre- to postimplementation, and multiway analyses of variance with post hoc pairwise t-tests with Bonferroni's correction were used to assess differences in scores by clinical role, setting, and specialty.Average Perceived Usefulness (PU) and adaptation scores were higher at AMC B than at AMC A, but similar pre- to postimplementation trends were observed at both sites. Perceptions of Quality of Work Life (QWL), PU, and User Control (UC) improved across both sites postimplementation, whereas Perceived Ease of Use and Cognitive Support and Situational Awareness declined. Ordering Providers, Registered Nurses, clinicians practicing in the Emergency Department setting, and Emergency Medicine, and Critical/Intensive Care specialists had statistically different scores across various constructs.After implementation of a new EHR system at two AMCs, clinical staff perceptions of quality of work life (QWL), perceived usefulness (PU), and user control (UC) generally improved, although perceptions of perceived ease of use and cognitive support declined.
Keywords: electronic health records and systems; implementation and deployment; user satisfaction; interface usability; cognitive support; burnout